Stakeholder governance to facilitate collaboration for a systemic circular economy transition: A qualitative study in the European chemicals and plastics industry - Felix Carl Schultz; Vladislav Valentinov; Julian Kirchherr; Robert Jaroslav Reinhardt; Ingo Pies (Business Strategy and the Environment, 2024)
Implementing the circular economy (CE) requires novel forms of stakeholder collaboration. While the contemporary literature on stakeholder theory is commonly characterized as “pro-business-oriented,” it remains ambiguous on how precisely stakeholder collaborations may pave the way for a systemic CE transition. By applying a qualitative-empirical research approach utilizing semi-structured interviews, this paper identifies three types of stakeholder governance for CE collaborations—(i) company-centric governance, (ii) industry-oriented governance, and (iii) cross-industry-oriented governance. Our contribution to stakeholder theory lies in examining how a systemic CE transition may bridge “the stakeholder-system divide.” We emphasize the unique role of innovative governance in ensuring the success of stakeholder relationships while highlighting how systemic changes of the business environment may give an impetus to stakeholder collaborations. We contribute to the CE literature by gaining the following insights into stakeholder collaborations in the European chemicals and plastics industry: (a) successful collaborations typically feature a variety of different stakeholders maintaining close mutual interactions; (b) a systemic CE transition calls for managerial strategies that are collectively governance-oriented rather than company-centric. This article thus sheds light on the criticality of stakeholder collaborations and collective-oriented governance strategies in fostering CE practices within the European chemicals and plastics industry highlighting that stakeholder collaborations for a CE need to be extended beyond immediate industrial and sectoral boundaries.
Keywords: 330; circular economy; collaboration; governance; plastics; stakeholder